Research on the impact of WTO trade policy review mechanism (TPRM) on the employability of Chinese college students during the economic structural transformation of its member countries - Yang, Haixia (Edelweiss Applied Science and Technology, 2024)
The WTO TPRM is a very important machinery where the WTO members submit for evaluation their trade policies and structures as well as their economic reforms. This research used secondary evidence from employment reports, government statistics and various industry research and employed expert policy and economic opinion. It analyses employment rates prior to and after the implementation of the “mass entrepreneurship and mass innovation” policy and the policy of integrated enterprise-school and university-enterprise. In total, the general sample consists of 500 students half of whom are male and the other half are female. The employment rates stands at an average of 78% among the students. In terms of the standard deviation, the figure is equal to 9.3% which he described as moderate variability of employment outcomes. . Similarly the analysis reveals a positive relationship between GPA, entrepreneurial intention and participation in vocational programs on employability ( p < 0. 001). The coefficient for entrepreneurial intention is especially significant (β = 0. 38), which means that students, who had entrepreneurial intentions, are more likely to be employed. Employment prospects for college students were found to be especially enhanced through adoption of the above policies showing a very strong implication of education and training to economic needs especially during structural change. This study has implication for policy formation and course offering for higher institutions of learning to enhance the employment status of graduates in the current world economy.